Penerapan Inovasi Teknologi dalam Meningkatkan Hasil Tangkapan Ikan bagi Nelayan di KUB Bugel - Aris Kusumo Diantoro; Roza Yusfiandayani; Hermanu Triwidodo; Zakiah Wulandari; Zulfatun Ruscitasari; Marosimy Millaty; Irwan Novianto; Fajar Sidik Abdullah Kelana (Institut Pertanian Bogor, 2024)
Service activities were conducted in the Bugel Peni II and III Joint Business Group (KUB) in Bugel Village, Kulonprogo Regency. Fishermen who join this group often do not get maximum catches because they face various obstacles, such as limited technology and unpredictable weather conditions. This community service aims to provide portable FAD innovations and determine the success of using portable FADs in fishermen's catches. Portable FADs are proposed for this service activity to provide a solution to minimize losses due to these obstacles. Portable FADs are an innovation that stimulates fish behavioral responses using sound waves with a specific frequency on an attractor, developing from the concept of conventional FADs. The implementation method begins with outreach to fishermen in the Bugel Peni II and III Joint Business Group (KUB) regarding the concept and benefits of portable FADs. Practical training was carried out on the installation and use of these tools and education regarding their positive impact on fish catches. In addition, data collection was carried out through direct observations in the field to understand fish responses to portable FADs. The positive impact of this service activity is that the application of portable FADs provides in-depth insight into the urgency of using technology to increase fish catches by fishermen. Apart from that, this service activity also provides important insight regarding the natural factors fishermen face in implementing portable FADs, such as weather uncertainty, increasingly scarce fish resources, and natural conditions, namely high waves, which are the main obstacles in achieving the expected results.